Open business model of eco-innovation for sustainability development: Implications for the open-innovation dynamics of Slovakia - Erika Loučanová; Miriam Olšiaková; Jana Štofková (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The paper presents the results of a survey aimed at evaluating the attitudes of Slovak respondents toward eco-innovation purchasing power supplied on the Slovak market to propose an open business model that would support such purchasing power to increase sustainability. The primary method applied in the research was the Kano model, by which we determined the attitudes of the respondents to the issue. Based on the findings and using the analytical-synthetic method, we subsequently processed a proposal for a business model for implementation of ecological innovation in Slovakia. This model used innovative marketing communication tools to increase interest in eco-innovation and products, and created a learning algorithm to influence customers' shopping behaviors. As a result of the research, we assumed that the main obstacles to increasing demand for eco-innovation and products were inexperience, cost, and lack of information held by respondents, and therefore it is necessary to build and improve customer relationships, in which, in addition to traditional forms of marketing, it is inevitable to use various innovative forms of corporate social responsibility to minimize these negatives.
Keywords: 650; business model; ecological innovation; innovation; open innovation; Slovakia